Perlindungan Hukum Terhadap Pemberi Pinjaman dalam Sistem Fintech Peer to Peer Lending (Studi pada Otoritas Jasa Keuangan Kantor Regional 5 Sumatera Bagian Utara) - Khadijah, Siti Nur; Sunarmi, Sunarmi; Ramadhan, M. Citra (Mahesa Research Center, 2023)
The problems discussed in this paper are How is the legal arrangement of lenders in the Peer To Peer Lending system, especially in the city of Medan where POJK is the foundation, How is the application of legal protection to lenders in the Peer to Peer Lending system, What are the obstacles and efforts on the part of the lender? lenders in the peer to peer lending financial technology system at OJK regional office 5, Northern Sumatra. The research method used by the author is normative juridical by finding and collecting data through library research from reading sources in the form of related legal books, legal expert opinions, related legislation, related websites, and interview results. The results of this study show that legal protection for Lenders can be realized in a preventive manner based on Article 29 of POJK Number 77/POJK.01/2016, namely by applying basic principles for Providers and repressive legal protection based on Article 37 of POJK Number 77/POJK.01/ 2016 concerning Information Technology-based Lending and Borrowing Services and Article 38 of POJK Number 1/POJK.07/2013 in conjunction with POJK Number 6/POJK.06/2022 concerning Consumer and Community Protection in the Financial Services Sector. when it comes from a system error.